The role of attentional control in moderating attentional bias towards game-related stimuli in individuals with a high tendency for internet gaming addiction - Heo, Yea-Ji; Lee, Gi-Eun; Lee, Jang-Han (Frontiers in Psychiatry, 2024)
Background: This study aimed to elucidate individual difference factors that modulate the attentional processing of game stimuli so that elucidate heterogeneity of extant findings. The current study examined whether individual differences in components of attentional control (AC shifting and focusing) moderated the link between internet gaming addiction symptom and attentional engagement to and disengagement biases from game-relevant cues. Methods: In total, 75 male undergraduate students who have played League of Legend (LOL) for more than 2 years completed well-established self-report questionnaires of internet gaming disorder symptoms and attentional control. The attentional bias toward game stimuli was measured for attentional engagement and disengagement using the attentional response to the distal vs proximal emotional information (ARDPEI) task.Results: The results revealed that attentional control was a significant moderator of the relationship between internet game addiction symptoms and attentional disengagement bias. Further analyses revealed that positive relationship between internet game addiction symptoms and attentional disengagement bias only among those with low levels of AC-shifting ability. Contrary to our expectations, AC-shifting also moderated the relationship between internet gaming disorder and attentional engagement bias. The positive relationship between internet game addiction symptoms and attentional engagement bias only appeared among those with low levels of AC-shifting ability. Individual differences in AC-focusing did not moderate the relationship between internet gaming disorder and any attentional bias.Conclusion: This study confirmed that the greater the symptoms of game addiction, the stronger the attentional bias, especially in individuals with low AC-shifting ability. Therefore, it is necessary to examine sub-factors of AC in understanding the nature of attentional bias mechanisms in the development of internet game addiction and consider it as a psychological intervention to improve attentional bias.